Respuesta :

Step-by-step explanation:

6a

Sn = n/2 [2a + (n-1) d]

(2Sn)/ n = 2a + (n - 1) d

2a + (n-1) d = (2Sn)/n

(n-1) d = (2Sn - 2a)/n

[tex]d = \frac{2sn \: - 2a}{(n(n - 1))} [/tex]

[tex]d = \frac{2(sn - a)}{ {n}^{2} - n} [/tex]

6b

[tex]d = \frac{2(56 - 25)}{ {32}^{2} - 32} [/tex]

d = ¹/16

7a.

E = (mv²)/2 + mgh

E = m( v²/2 + gh)

E/m = v²/2 + gh

E/m - gh = v²/2

2(E/m - gh) = v²

so

[tex]v = \sqrt{2( \frac{e}{m} - gh)}[/tex]

7b.

[tex]v = \sqrt{2( \frac{4900}{20} - 9.8 \times 15)}[/tex]

v = 14 m/s

ACCESS MORE